THE HEDONIST’S EMOTIONS - Deonna, Julien; Teroni, Fabrice (Les ateliers de l'éthique / The Ethics Forum, 2022)
This paper explores the compelling hedonistic intuition that emotions affect happiness because they are states of pleasure and displeasure. The discussion focusses on two constraints on a plausible version of hedonism and explains which accounts of the emotions satisfy these constraints. Section 1 revolves around the nonalienation constraint: the constituents of a subject’s happiness must engage him or her. We argue that the intuition that emotions have prudential value presupposes that emotions are forms of engagement, a condition that only some accounts of the emotions satisfy. Section 2 centres around the unity constraint: if we acknowledge a great variety of (dis)pleasures, we still need to understand what makes all of them (dis)pleasures. Conceiving of the emotions as forms of engagement, we contend, allows us to resolve the difficulties concerning the variety and unity of (dis)pleasures that weigh on traditional hedonism. In section 3, we defend the form of affective hedonism that has emerged. We argue that the approach can be extended from emotions to other affective states and that the central role we give to action tendencies in our conception of affectivity does not call into question the idea that emotions contribute to happiness because of their hedonic value.